The Charter and By-Laws of the Borough of Wallingford Page 55 (1882) §15 - (:unkn) unknown (General Publisher, 1882)
Prohibited the discharge of any pistol, gun, cannon, or other fire-arm in any street, park, or public ground. Violators fined not exceeding twenty-five dollars.
--
Keywords: DISCHARGE